Advances in Computer Science and Information Engineering Volume 2 - Jin, David; Lin, Sally; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
CSIE2012 is an integrated conference concentrating its focus on Computer Science and Information Engineering . In the proceeding, you can learn much more knowledge about Computer Science and Information Engineering of researchers from all around the world. The main role of the proceeding is to be used as an exchange pillar for researchers who are working in the mentioned fields. In order to meet the high quality of Springer, AISC series, the organization committee has made their efforts to do the following things. Firstly, poor quality paper has been refused after reviewing course by anonymous referee experts. Secondly, periodically review meetings have been held around the reviewers about five times for exchanging reviewing suggestions. Finally, the conference organizers had several preliminary sessions before the conference. Through efforts of different people and departments, the conference will be successful and fruitful.
From the Contents: Vehicle Style Recognition Based on Image Processing and Neural Network -- Feature Model Application in No-Mold-Drawing Control -- Research of E-commerce Based on Cloud Computing -- Study on Chaos-Based Weak Signal Detection Method with Duffing Oscillator -- The Application of Association Rule Mining in CRM based on Formal Concept Analysis -- The Design of Data Collection Methods in Wireless Sensor Networks based on Formal Concept Analysis -- The Research of Network Management System Based on Mobile Agent and SNMP Technology -- A Research of PLD Training for IT Applications -- Terminal Sliding Mode Control for STT Missile Based on RBF Neural Network -- Design of Broadband Receiver in Battlefield Electromagnetic Spectrum Monitoring System.
Keywords: Engineering; Engineering mathematics; Engineering; Computational Intelligence; Computer Engineering; Appl.Mathematics/Computational Methods of Engineering